Β-VO2/carbon nanotubes core-shelled microspheres and their applications for advanced cathode in aqueous zinc ion batteries. (20th December 2021) - Fan, Xiankai; Wen, Xiaoyu; Tang, Yuan; Zhou, Wei; Xiang, Kaixiong; Chen, Han
Abstract: The dissolution of cathode material is imminently resolved in the commercial application of aqueous zinc-ion batteries (ZIBs). The β-VO2 /carbon nanotubes (CNTs) microspheres with various constructions were acquired by the ultrasonic atomization depositions. β-VO2 /CNTs core-shelled microspheres, which the VO2 cores are homogeneously covered by CNTs shells, can suppress more effectively the VO2 dissolution. The β-VO2 / CNTs core-shelled microspheres exhibited a higher capacity of 380 mAh g −1 at the current density of 0.05 A g −1, and maintained a steadier capacity retention of 80% after 7800 cycles. The construction of perfect CNTs shells is considerably effective to restrain the dissolution of β-VO2 and improve the cycle stability.